The Influence of Familyâ€™s Support for Students English Learning Achievement at Elementary School Age - Arum Priadi; Rafa Aly Nuha (English Language Teaching Educational Journal, 2019)
This research is carried out 1) to find out whether there is a positive and significant correlation between familyâ€™s support and studentsâ€™ English learning achievement and 2) to find out whether there is a difference between students who get the support and students who do not get the support from family. This research belongs to correlational research with quantitative approach. It was held at SD Negeri Kaliwungu 05, Cilacap in academic year 2017/2018. The sample of this research is the fifth grade students at SD Negeri Kaliwungu 05. The data collecting techniques of the research were questionnaire, documentation, and interview. Then in analyzing the data, the researchers used Product Moment Formula with computer application SPSS. The result findings show that : 1) familyâ€™s support (X) level is in â€œsupportedâ€ level at SD Negeri Kaliwungu 05. 2) The level of studentsâ€™ English learning achievement (Y) at fifth grade of SD Negeri Kaliwungu 05 is in â€œfairâ€ level. 3) there is positive and significant correlation between familyâ€™s support and studentsâ€™ English learning achievement of the fifth year students of SD Negeri Kaliwungu 05, Cilacap, shown by the coefficient correlation 0.508.